Unraveling the complexities of plant cell wall biosynthesis for enhanced biofuel production: a molecular genetics perspective - Jyoti Prakash Sahoo; Bhagyashree Priyadarshini; Jayanta Kumar Nayak; Subhashree Subhadarshini; Akshaya Kumar Nayak; Samikshya Malik (Academia Molecular Biology and Genomics)
The molecular genetics of plant cell wall synthesis is a critical area of research with significant implications for biofuel production. The plant cell wall, a complex network of biopolymers including cellulose, hemicellulose, pectin, and lignin, represents a substantial portion of plant biomass and is fundamental to plant structure and growth. Advances in functional genomics and molecular genetics have led to the identification of key genes and enzymes involved in the biosynthesis and remodeling of these polysaccharides. Notably, the biosynthesis pathways of matrix polysaccharides are well understood, providing a foundation for manipulating their structure in planta to enhance biomass properties. Genetic engineering approaches, including the modification of genes related to lignin biosynthesis, have shown promise in improving the efficiency of saccharification, a critical step in converting plant biomass to fermentable sugars for bioethanol production. Techniques such as transgenic approach, quantitative trait locus (QTL) mapping and association mapping are also employed to identify and manipulate genes associated with cell wall polymer synthesis, offering potential for marker-assisted breeding. Additionally, advanced analytical tools such as systems biology and synthetic biology approaches facilitate the detailed structural analysis of cell wall polymers, enabling targeted modifications to optimize cell wall properties for bioenergy applications. Collectively, these advancements position plant cell wall biosynthesis research at the forefront of developing sustainable biofuel production strategies for advancing the energy sector.